RENDERING LEXICAL AND STYLISTIC FEATURES OF J. D. SALINGER’S “UNCLE WIGGILY IN CONNECTICUT” IN THE UKRAINIAN TRANSLATIONS - Коляда, Еліна; Вецкур, Тетяна (Current Issues of Foreign Philology, 2021)
The paper presents the results of comparative analysis of two Ukrainian translations of J. D. Salinger's story entitled “Uncle Wiggily in Connecticut”. The data were analyzed in order to study the opposition “original-oriented vs. reader-oriented” translation. The study was undertaken on several levels. Peculiarities of graphons rendering were traced at the phono-graphic level. The lexical level comprises culture-specific vocabulary, invectives and slang. The lexico-semantic level includes metaphors, similes, epithets and antonomasia. The authors state that translation of culture-specific vocabulary depends on the extent to which foreign culture realities are integrated into the readers’ culture. Where the translator fails to convey the author’s signature idiolect, e.g. graphons, the literary piece register becomes more neutral and meaningful details are lost. Moreover, the translated work of fiction can be neutralized and euphemized due to censorship and ideology. The authors conclude that successful translation can be defined in terms of its preserved authentic features and accessibility for the readers.